2020
DOI: 10.1002/pon.5438
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress in breast cancer survivors diagnosed at a young age

Abstract: Objective: Young breast cancer patients experience greater psychosocial distress compared with older patients, which raises concern for their risk of posttraumatic stress disorder (PTSD). We sought to characterize the prevalence of clinically significant symptoms of PTSD and associated factors among breast cancer survivors diagnosed at a young age. Methods: The Young Women's Breast Cancer Study, an ongoing prospective cohort study, enrolled 1302 women diagnosed with breast cancer at age ≤ 40 between 2006 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 38 publications
4
23
0
Order By: Relevance
“…Despite the SDS score, our study identified several other common correlates for PTSS in both patients with depression and non-depressed controls. We found that the IES-R total score was positively associated with SAS score in both depression and non-depression groups, which was consistent with previous studies on breast cancer survivors ( 53 ). Another study on American adolescents also showed that anxiety was the most common psychiatric comorbidities in hospitalized adolescent patients with PTSS ( 54 ).…”
Section: Discussionsupporting
confidence: 92%
“…Despite the SDS score, our study identified several other common correlates for PTSS in both patients with depression and non-depressed controls. We found that the IES-R total score was positively associated with SAS score in both depression and non-depression groups, which was consistent with previous studies on breast cancer survivors ( 53 ). Another study on American adolescents also showed that anxiety was the most common psychiatric comorbidities in hospitalized adolescent patients with PTSS ( 54 ).…”
Section: Discussionsupporting
confidence: 92%
“…Whereas testicular cancer survivors showed a comparably low level of full PTSD with a prevalence of 4.5%[ 17 ], the two studies including melanoma patients showed numbers as high as 48%[ 14 , 27 ]. For breast cancer survivors, the prevalence ranged from 6.3%[ 16 ] to 18%[ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The greater number of social stressors experienced by Black women has been hypothesized to influence breast cancer survival disparities through psychosocial stress and related physiologic effects ( Williams et al, 2016 ; Saini et al, 2019 ; Coughlin, 2019 ). Studies of stress among breast cancer survivors, however, have found little evidence of associations involving social factors, including race/ethnicity and socioeconomic status ( Golden-Kreutz et al, 2005 ; Syrowatka et al, 2017 ; Stanton et al, 2015 ; Vazquez et al, 2020 ). For example, Golden-Kreutz et al, found no correlation between race, educational attainment, or household income and perceived stress among women surgically treated for breast cancer.…”
Section: Discussionmentioning
confidence: 99%